Pharmacokinetics of Ambroxol Sustained Release (Mucosolvan(®) Retard) Compared with Other Formulations in Healthy Volunteers - Ollier, Celine (Pulm Ther, 2020)
INTRODUCTION: Ambroxol is used in the treatment of acute and chronic respiratory conditions characterized by abnormal mucus secretion and impaired mucus transport and is available in a variety of formulations. This study aimed to compare the steady-state (SS) pharmacokinetic characteristics of extended-release (ER) 75-mg retard capsules with two immediate-release (IR) formulations (60-mg effervescent tablets and 30-mg tablets) over a 24-h period. METHODS: An open-label, randomized, three-period, six-sequence crossover study was conducted in healthy volunteers aged 18–45 years who had a normal body mass index. The test (ER 75-mg retard capsule once daily) and reference treatments (half of IR 60-mg effervescent tablet twice daily or 30-mg IR tablet twice daily) were administered on days 1–5 of each treatment period. Meals were standardized and concomitant therapy was prohibited. Blood samples for pharmacokinetic assessment were collected on day 5 (SS) of each treatment period. The co-primary endpoints were exposure (AUC(SS 0–24)) and maximum plasma level (C(max SS)). RESULTS: Twenty-four participants received ambroxol (male n = 13, 54.2%; mean ± standard deviation [SD] age 25.0 ± 6.4 years) and 23 completed the study. ER retard capsules provided similar AUC(SS 0–24) compared to IR tablets (geometric means ratio [GMR] 110.7%; 90% confidence interval [CI] 99.8%, 122.7%) and effervescent tablets (GMR 106.9%; 90% CI 100.3%, 114.0%). ER retard capsules provided similar C(max SS) compared to IR tablets (GMR 84.7%, 90% CI 77.0%, 93.3%), and lower C(max SS) compared to effervescent tablets (GMR 80.9%, 90% CI 73.9%, 88.6%). Time to C(max SS) (t(max SS)) was longer with ER retard capsules (6.0 h) than with IR tablets (2.0 h) or effervescent tablets (1.0 h). CONCLUSIONS: ER ambroxol 75-mg retard capsules given once daily showed a similar pharmacokinetic profile to IR ambroxol formulations and therefore can be used instead of these in the treatment of respiratory conditions. CLINICALTRIALS.GOV IDENTIFIER: NCT02036775. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s41030-020-00116-7) contains supplementary material, which is available to authorized users.